Emerging trends in cervical cancer incidence among younger Taiwanese generations: an urban–rural comparison - Ya-Xuan Wu; Yi-Chu Chen; Jing-Rong Jhuang; Chun-Ju Chiang; Wen-Chung Lee (Annals of Medicine)
Background Despite global declines in cervical cancer incidence, certain regions observe unexpected rising trends among younger generations.Methods This study uses the age–period–cohort model to examine long-term incidence trends of invasive cervical cancer in Taiwan. Data were sourced from the Taiwan Cancer Registry.Results From 2000 to 2019, both urban and rural areas of Taiwan saw a marked decrease in incidence rates, a trend largely attributed to the cytology-based screening program introduced in 1995. Yet, rising incidence rates emerged in younger Taiwanese generations, specifically those born post-1975 in urban and post-1980 in rural settings. The 1990-born urban cohort faced a risk 1.9 times higher than their 1975-born counterparts, while the risk for the 1990-born rural cohort was 1.4 times greater than those born in 1980. In addition, post-1980 urban cohorts exhibited greater risks than their rural counterparts.Conclusions The rising trends in cervical cancer incidence among younger Taiwanese generations may be influenced by factors such as increased sexual permissiveness and urbanization. Although current prevention efforts, such as human papillomavirus vaccination, are noteworthy, there is a need for ongoing surveillance and improved strategies that specifically target recent cohorts.